7x+3x-7=4x-17-6

Simple and best practice solution for 7x+3x-7=4x-17-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3x-7=4x-17-6 equation:


Simplifying
7x + 3x + -7 = 4x + -17 + -6

Reorder the terms:
-7 + 7x + 3x = 4x + -17 + -6

Combine like terms: 7x + 3x = 10x
-7 + 10x = 4x + -17 + -6

Reorder the terms:
-7 + 10x = -17 + -6 + 4x

Combine like terms: -17 + -6 = -23
-7 + 10x = -23 + 4x

Solving
-7 + 10x = -23 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-7 + 10x + -4x = -23 + 4x + -4x

Combine like terms: 10x + -4x = 6x
-7 + 6x = -23 + 4x + -4x

Combine like terms: 4x + -4x = 0
-7 + 6x = -23 + 0
-7 + 6x = -23

Add '7' to each side of the equation.
-7 + 7 + 6x = -23 + 7

Combine like terms: -7 + 7 = 0
0 + 6x = -23 + 7
6x = -23 + 7

Combine like terms: -23 + 7 = -16
6x = -16

Divide each side by '6'.
x = -2.666666667

Simplifying
x = -2.666666667

See similar equations:

| 5x=195 | | 2(x+4)+5=2x+3 | | 3(3+6x)=81 | | -1.75=2.21 | | 4x-5=7x-29 | | (15x^2-5x+2)-4(3x^2+6x-7)= | | 6(4+1.5x)-12=66 | | 10i+2yi=0 | | -2[4-(3b+2)]=-2(3b+6) | | -9/6=11/12 | | 12n+3+3n=15+7n-2 | | 56/(-4) | | cos^2x+4cosx=3sin^2x | | 2x+4(x-3)=60 | | 2-n=8 | | 5i-6x=10yi+2 | | 5t-5/-10+70 | | -w+7=-3 | | 1-3m-8=-10 | | x(5x-5)=(5x+4)(x-1) | | 1-3m-8= | | 2x+17-4x=34 | | 8a+2(a+3)+12=4a+66 | | (3/4)-(1/2n)=(4/5) | | f+3=2f-5 | | 4x-10=x-46 | | 4x+6y=230 | | 8=-5-8x-5x | | 3x-7-5=-3 | | 14y+81=-y | | 18+m=9 | | n+8+4=19 |

Equations solver categories